# Download e-book for iPad: Abstract Algebra II by Randall R. Holmes

By Randall R. Holmes

**Read or Download Abstract Algebra II PDF**

**Best linear books**

**Download PDF by A. Cheremensky, V.N. Fomin: Operator Approach to Linear Control Systems**

The assumption of optimization runs via such a lot elements of keep watch over idea. the best optimum controls are preplanned (programmed) ones. the matter of creating optimum preplanned controls has been commonly labored out in literature (see, e. g. , the Pontrjagin greatest precept giving helpful stipulations of preplanned keep watch over optimality).

**Ryszard Engelking's Theory of dimensions, finite and infinite PDF**

Magnet hyperlink : magnet:? xt=urn:btih:a4076e60212dc4c9bc12b13c40941552da202bd6&dn=Theory%5Fof%5FDimensions%5FFinite%5Fand%5FInfinite-Ryszard%5FEngelking-Vol. 10%5FHeldermann%5FVerlag-1995. djvu&tr=udp%3A%2F%2Ftracker. openbittorrent. com%3A80%2Fannounce&tr=udp%3A%2F%2Ftracker. publicbt. com%3A80&tr=udp%3A%2F%2Ftracker.

- Algebraic and Analytic Methods in Representation Theory
- Photonics: Linear and Nonlinear Interactions of Laser Light and Matter, Second edition
- Linear Dynamic Systems and Signals
- Introduction to Matrices and Linear Transformations

**Extra resources for Abstract Algebra II**

**Sample text**

Suppose that also f (x) = q (x)g(x) + r (x) with q (x), r (x) ∈ F [x] and deg r (x) < deg g(x). We have r(x) − r (x) = [f (x) − q(x)g(x)] − [f (x) − q (x)g(x)] = [q (x) − q(x)]g(x). If q(x) = q (x), then we get the contradiction deg g(x) > max{deg r(x), deg r (x)} ≥ deg[r(x) − r (x)] = deg[(q (x) − q(x))g(x)] = deg[q (x) − q(x)] + deg g(x) ≥ deg g(x), since deg[q (x) − q(x)] ≥ 0. Therefore, q (x) = q(x) and the earlier equation gives r (x) = r(x) as well. This completes the proof. 4 Zeros of a polynomial Let R be a commutative ring and let f (x) = ni=0 ai xi be a polynomial over R.

Define ϕ : S → (S +I)/I by ϕ(s) = s+I. Then ϕ is a homomorphism (it is simply the restriction to S of the canonical epimorphism R → R/I). For s ∈ S we have s ∈ ker ϕ ⇐⇒ ϕ(s) = I ⇐⇒ s + I = I ⇐⇒ s ∈ S ∩ I, so ker ϕ = S ∩ I. Let x ∈ (S + I)/I. Then x = (s + a) + I = s + I for some s ∈ S and a ∈ I, and we have ϕ(s) = s + I = x, so ϕ is surjective. 1), S/(S ∩ I) = S/ ker ϕ ∼ = im ϕ = (S + I)/I, and the proof is complete. 4 Third Isomorphism Theorem Let R be a ring and let I and J be ideals of R with J ⊇ I.

Let I be an ideal of R. An element r of R is in the kernel of π if and only if I = π(r) = r + I, which occurs if and only if r ∈ I. Therefore, I = ker π. 6 Homomorphism is injective iff kernel is trivial Here is a reminder of a useful criterion from group theory for checking injectivity of a homomorphism. Let ϕ : R → R be a homomorphism of rings. 1 Theorem. ϕ is injective if and only if ker ϕ = {0}. Proof. Assume that ϕ is injective. Let r ∈ ker ϕ. Then ϕ(r) = 0. 3. So ϕ(r) = ϕ(0) and injectivity of ϕ gives r = 0.

### Abstract Algebra II by Randall R. Holmes

by Edward

4.4